Odpowiedzi

2009-12-15T16:29:23+01:00
A) 2x-14=4(x-5)
2x-14=4x-20
2x-4x=-20+14
-2x=-6/:-2
x=3

b)(12x-9):3=5x
12x-9:3=5x
12x-3=5x
12x-5x=3
7x=3/:7
x= 3/7

c)(2x-3)²=4x²
4x²-12x+9=4x²
4x²-4x²-12x=-9
-12x=-9/:-12
x=9/12=3/4

2009-12-15T16:29:25+01:00
A)2x-14=4(x-5)
2x-14=4x-20
6=2x
x=3

b) (12x-9):3=5x
12x:3 -9:3=5x
4x-3=5x
-3=x
x=-3

c)(2x-3)²=4x²
4x²+9-12x=4x²
9=12x
x=9/12
x=3/4
2009-12-15T21:26:09+01:00
A) 2x - 14 = 4 (x-5)
2x - 14 = 4x - 9
-14 + 9 = 4x - 2x
-5 = 2x | : 2
-2,5 = x

b) (12x - 9) : 3 = 5x
4x - 3 = 5x
-3 = 5x - 4x
-3 = x

c) (2x-3)² = 4x²
4x²-9 = 4x²
4x² - 4x² = 9